The Alterations in Mitochondrial Dynamics Following Cerebral Ischemia/Reperfusion Injury - Jirapong Vongsfak; Wasana Pratchayasakul; Nattayaporn Apaijai; Tanat Vaniyapong; Nipon Chattipakorn; Siriporn C. Chattipakorn (MDPI AG, 2021)
Cerebral ischemia results in a poor oxygen supply and cerebral infarction. Reperfusion to the ischemic area is the best therapeutic approach. Although reperfusion after ischemia has beneficial effects, it also causes ischemia/reperfusion (I/R) injury. Increases in oxidative stress, mitochondrial dysfunction, and cell death in the brain, resulting in brain infarction, have also been observed following cerebral I/R injury. Mitochondria are dynamic organelles, including mitochondrial fusion and fission. Both processes are essential for mitochondrial homeostasis and cell survival. Several studies demonstrated that an imbalance in mitochondrial dynamics after cerebral ischemia, with or without reperfusion injury, plays an important role in the regulation of cell survival and infarct area size. Mitochondrial dysmorphology/dysfunction and inflammatory processes also occur after cerebral ischemia. Knowledge surrounding the mechanisms involved in the imbalance in mitochondrial dynamics following cerebral ischemia with or without reperfusion injury would help in the prevention or treatment of the adverse effects of cerebral injury. Therefore, this review aims to summarize and discuss the roles of mitochondrial dynamics, mitochondrial function, and inflammatory processes in cerebral ischemia with or without reperfusion injury from in vitro and in vivo studies. Any contradictory findings are incorporated and discussed.